2018
DOI: 10.1186/s13550-018-0386-4
|View full text |Cite
|
Sign up to set email alerts
|

External radiation exposure, excretion, and effective half-life in 177Lu-PSMA-targeted therapies

Abstract: BackgroundProstate-specific membrane antigen (PSMA)-targeted therapy with 177Lu-PSMA-617 is a therapeutic option for patients with metastatic castration-resistant prostate cancer (mCRPC). To optimize the therapy procedure, it is necessary to determine relevant parameters to define radiation protection and safety necessities. Therefore, this study aimed at estimating the ambient radiation exposure received by the patient. Moreover, the excreted activity was quantified.ResultsIn total, 50 patients with mCRPC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 49 publications
1
40
0
7
Order By: Relevance
“…Several factors limit the effectiveness of b-particle radiotherapy, including the modest linear energy transfer of b-particles (6) and poor pharmacokinetics, particularly insufficient dose delivery to the tumor. This limitation is reflected by the recent report that 50% of injected activity of 177 Lu-PSMA-617 is excreted within 4 h of administration and that by 12 h, nearly 70% of the activity has been excreted (7). It has been reported that there is a significantly positive, even logarithmic, relationship between response rate and dose delivered to the tumor in patients treated with 177 Lu-DOTATATE (8), and the high dose delivered to prostate cancer metastases is credited for the reported response of these lesions after radioligand therapy with 177 Lu-PSMA-I&T (4).…”
mentioning
confidence: 99%
“…Several factors limit the effectiveness of b-particle radiotherapy, including the modest linear energy transfer of b-particles (6) and poor pharmacokinetics, particularly insufficient dose delivery to the tumor. This limitation is reflected by the recent report that 50% of injected activity of 177 Lu-PSMA-617 is excreted within 4 h of administration and that by 12 h, nearly 70% of the activity has been excreted (7). It has been reported that there is a significantly positive, even logarithmic, relationship between response rate and dose delivered to the tumor in patients treated with 177 Lu-DOTATATE (8), and the high dose delivered to prostate cancer metastases is credited for the reported response of these lesions after radioligand therapy with 177 Lu-PSMA-I&T (4).…”
mentioning
confidence: 99%
“…To illustrate, the delivery of 177 Lu-PSMA is resource intensive: it requires a radiolabeled intravenous preparation and careful handling and specialist staff together with quality control and post-administration observation [4]. Although in some countries, outpatient administration of radionuclide therapy is allowed, most countries, certainly within Europe, legally prescribe hospitalization for administration [24]. Such hospitalization requires dedicated radiation protection facilities, in which patient rooms are required to have dedicated sanitary facilities and shielded walls [13].…”
Section: Operational Readinessmentioning
confidence: 99%
“…It is critical that hospitals consciously pay attention to the ecological responsibility and safety of 177 Lu-PSMA [24]. The processing of hazardous medical disposal and the emission of metabolized substance activity, including appropriate storage space, requires radiation protection regarding public and environmental exposure [26].…”
Section: Environmental Managementmentioning
confidence: 99%
“…The magnitude of the radiation exposure and resultant radiation risk in all these scenarios will be higher from day-case patients compared to that from in-patients due to the higher external dose rates associated with patient contact earlier after administration [ 2 , 3 ]. Additionally, minimising transfer of radioactive contamination from urine, faeces, sweat or saliva in the home will be more challenging to achieve as the earlier discharge also results in higher levels of excretion occurring in the home [ 4 ].…”
Section: Day Case Considerationsmentioning
confidence: 99%